Abrotoxyela gen. nov. (Insecta, Hymenoptera, Xyelidae) from the Middle Jurassic of Inner Mongolia, China - Gao, Taiping; Ren, Dong; Shih, Chungkun (Zootaxa, 2009)
Abrotoxyela gen. nov. of Xyelidae and Abrotoxyela lepida sp. nov. and Abrotoxyela multiciliata sp. nov. are described from the Middle Jurassic Jiulongshan Formation of Daohugou Village, Inner Mongolia, China. The new genus is established on basis of the triple-branched vein Sc of the fore wing with first branch intersecting C at nearly 1/4 of its length; Sc terminates at C distal to the origin of Rs; and basal section of Rs approximately as long as that of M.